TRAFFIC CAPACITY ANALYSIS OF EXISTING CONDITIONS WITH THE EFFECT OF ADDITIONAL COAL TRANSPORTATION TARGETS ON THE TANJUNG ENIM - TARAHAN RAILWAY LINE - Setyaji, Arif; Pamursari, Nurmagita; Sari, Nurwanda (Journal of Science and Applicative Technology, 2024)
The production volume target from 24.8 million tons in 2020 to 29.5 million tons in 2021 underlies the optimization of transportation availability in distributing coal mining products carried out by PT Bukit Asam Persero in achieving the growing target until 2023. In 2021, the Company will increase investment in developing business diversification, downstream coal. The railway network in Sumatra has a strategic role in serving the distribution of coal transportation. The railway line, which is directly connected to the location of the mining plant to port access and the availability of locomotive facilities and wagons that are very adequate, is an attractive option for mining companies and freight forwarders to establish coal transportation cooperation by rail. To meet the Babaranjang train tonnage target of 52 tons / year in accordance with the target of PT Bukit Asam (Persero), the Loop rail line design at TLS T4 PT Bukit Asam Muara Enim used the most effective classification. From the calculation results, 55 train trips are required per day to transport the production target of 57 tons / year in 2023. It is necessary to pay attention to the adequacy of the rail track from the TLS loop to Tanjung Enim Baru here it is necessary to conduct a study regarding the traffic from TLS to Tanjung Enim Baru because the number of trains set per day is 55 sets.